2022
DOI: 10.1186/s12889-022-13701-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of seasonal variations on household water security and burden of diarrheal diseases among under 5 children in an urban community, Southwest Nigeria

Abstract: Background Household water security encompasses water-related factors that pose threats to public health at the household level. It presents a reliable access to water in sufficient quantity and quality towards meeting basic human needs. This study assessed the dynamics of seasonal variations in household water security and the association between household water security and diarrheal disease across dry and wet seasons in an urban settlement in Southwest Nigeria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Akinyemi et al. 42 reported a pronounced intensity of insecurity in household water during the dry season compared with that in the rainy season in a recent panel study designed to examine the effect of seasonal variations on household water security in an urban community in southwest Nigeria. Rabiu et al., 43 in a study on the microbiological quality of water from Watari Dam, Kano State, Nigeria, reported higher bacterial counts during the dry season than the wet season, but in a recent study carried out in Ibadan, more pathogens were recorded during the wet season.…”
Section: Discussionmentioning
confidence: 99%
“…Akinyemi et al. 42 reported a pronounced intensity of insecurity in household water during the dry season compared with that in the rainy season in a recent panel study designed to examine the effect of seasonal variations on household water security in an urban community in southwest Nigeria. Rabiu et al., 43 in a study on the microbiological quality of water from Watari Dam, Kano State, Nigeria, reported higher bacterial counts during the dry season than the wet season, but in a recent study carried out in Ibadan, more pathogens were recorded during the wet season.…”
Section: Discussionmentioning
confidence: 99%